The Application of AS 61508 to Road Tunnel Fire and Life Safety Systems - M Taylor (The Australasian Institute of Mining and Metallurgy, 2011)
The Project Specification and Technical Requirements documents associated with several recent large road tunnel projects within Australia have specified the application of AS/IEC 61508 – FunctionalSafety of Electrical/Electronic/Programmable Electronic Safety Related Systems at very high performance levels for the various control and fire life safety systems associated with such facilities.This paper seeks to explore the implications of referencing this standard within the road tunnel services context in terms of practicality, complexity and cost, whilst providing some examples of how a high safety integrity level (SIL) level can theoretically be achieved given current hardware availability.